Pharmacokinetic Evaluations of the Co-Administrations of Vandetanib and Metformin, Digoxin, Midazolam, Omeprazole or Ranitidine - Johansson, Susanne; Read, Jessica; Oliver, Stuart; Steinberg, Mark; Li, Yan; Lisbon, Eleanor; Mathews, David; Leese, Philip T.; Martin, Paul (Clinical pharmacokinetics, 2014)
Background and Objective Vandetanib is a selective inhibitor of vascular endothelial growth factor receptor (VEGFR), epidermal growth factor receptor (EGFR) and rearranged during transfection (RET) signalling, indicated for the treatment of medullary thyroid cancer. We investigated potential drug–drug interactions between vandetanib and metformin [organic cation transporter 2 (OCT2) substrate; NCT01551615]; digoxin [P-glycoprotein (P-gp) substrate; NCT01561781]; midazolam [cytochrome P450 (CYP) 3A4 substrate; NCT01544140]; omeprazole (proton pump inhibitor) or ranitidine (histamine H 2 -receptor antagonist; both NCT01539655). Methods Four open-label, phase I studies were conducted in healthy volunteers: n = 14 (metformin), n = 14 (digoxin), n = 17 (midazolam), n = 16 (omeprazole), n = 18 (ranitidine). Three of these comprised the following regimens: metformin 1000 mg ± vandetanib 800 mg, midazolam 7.5 mg ± vandetanib 800 mg, or digoxin 0.25 mg ± vandetanib 300 mg. The randomized study comprised vandetanib 300 mg alone and then either (i) omeprazole 40 mg (days 1–4), and omeprazole + vandetanib (day 5); or (ii) ranitidine 150 mg (day 1), and ranitidine + vandetanib (day 2). The primary objective assessed metformin, digoxin, midazolam and vandetanib pharmacokinetics. Results Vandetanib + metformin increased metformin area under the plasma concentration–time curve from zero to infinity (AUC 0–∞ ) and maximum observed plasma concentration (C max ) by 74 and 50 %, respectively, and decreased the geometric mean metformin renal clearance (CL R ) by 52 % versus metformin alone. Vandetanib + digoxin increased digoxin area under the concentration-time curve from zero to the last quantifiable concentration (AUC 0–last ) and C max by 23 and 29 %, respectively, versus digoxin alone, with only a 9 % decrease in CL R . Vandetanib had no effect on midazolam exposure. Vandetanib exposure was unchanged during co-administration with omeprazole/ranitidine. Treatment combinations were generally well tolerated. Conclusion Patients receiving vandetanib with metformin/digoxin may require additional monitoring of metformin/digoxin, with dose adjustments where necessary. Vandetanib with CYP3A4 substrates or omeprazole/ranitidine is unlikely to result in clinically relevant drug–drug interactions.